On relevance, decolonisation and community engagement: The role of university intellectuals - Msila, V. (South African Journal of Higher Education, 2023)
This article examines the role of intellectuals in building and sustaining engaged African universities. These intellectuals have enormous roles in conjuring and nourishing the vision of enhanced, working institutions. As guardians of nationalism and progress, they cannot and should not eschew aspects such as the politics of identity, social consciousness as well as other pertinent philosophies. It would, for example, be inconceivable to contemplate the African institutions’ transformation without reflecting on concepts such as decolonisation and Pan‑Africanism, and these are scrutinised in the ensuing discussion. The article also explores the dynamic, painstaking roles that intellectuals have to engage in. The topic on relevance and community engagement will always be important as debates on decolonisation continue. Intellectuals inside and outside the academe will always be useful in transforming society and its institutions. Yet, the work of intellectuals and their influence are buoyed by the characteristics that intellectuals possess. Whether one is a denialist, loyalist, knower or planetary intellectual will inform society of their role in mobilising communities and universities for transformation. Furthermore, the article examines the role of all intellectuals rather than those based at higher education institutions only. Oftentimes when society speaks of intellectuals, it is not the subaltern that they refer to – people outside the university who have been dominated by the hegemony displayed in higher education institutions regarding knowledge ownership. Antonio Gramsci postulates that this hegemony encompasses cultural, moral and ideological leadership over the subaltern. The findings in this debate demonstrate that it will be conscientious and selfless intellectuals who will fortify intellectual engagement for transformation of higher education institutions. The conclusions demonstrate that intellectuals have a judicious responsibility in safeguarding stability and meaningful transformation